A Checklist of Mosses for the North-Eastern Region of the Langkawi Islands, Peninsular Malaysia with Additional Records for the Langkawi Group of Islands - Mohamed, Haji; Kien-Thai, Yong (Malaysian Journal of Science, 2017)
A checklist comprising 89 species and 1 variety in 48 genera and 22 families of mosses and one species of hornwort have been compiled as a result of two bryological expeditions carried out in the north-eastern part of Langkawi Islands. Ten species are reported as new additions to Langkawi Islands. These bring the total number of mosses reported for the Islands to 137 species and 1 subspecies, 1 variety in 60 genera and 24 families. This total represents 27.4 % of the moss taxa which have been reported for Peninsular Malaysia. The North Eastern part of Langkawi Islands supports a higher percentage of mosses than Tioman Island (18.4%) and Pangkor Island (10.6%).